Comparison of Single-Walled and Multiwalled Carbon Nanotubes Durability as Pt Support in Gas Diffusion Electrodes. (27th December 2012) - Asgari, Mehdi; Lohrasbi, Elaheh
Abstract : Durability of single-walled (SWCNT) and multiwalled carbon nanotubes (MWCNT) as Pt supports was studied using two accelerated durability tests (ADTs), potential cycling and potentiostatic treatment. ADT of gas diffusion electrodes (GDEs) was once studied during the potential cycling. Pt surface area loss with increasing the potential cycling numbers for GDE using SWCNT was shown to be higher than that for GDE using MWCNT. In addition, equilibrium concentrations of dissolved Pt species from GDEs in 1.0 M H2 SO4 were found to be increased with increasing the potential cycling numbers. Both findings suggest that Pt detachment from support surface plays an important role in Pt surface loss in proton exchange membrane fuel cell electrodes. ADT of GDEs was also studied following the potentiostatic treatments up to 24 h under the following conditions: argon purged, 1.0 M H2 SO4, 60°C, and a constant potential of 0.9 V. The subsequent electrochemical characterization suggests that GDE that uses MWCNT/Pt is electrochemically more stable than other GDE using SWCNT/Pt. As a result of high corrosion resistance, GDE that uses MWCNT/Pt shows lower loss of Pt surface area and oxygen reduction reaction activity when used as fuel cell catalyst. The results also showed that potential cycling accelerates the rate of surface area loss.